Supramolecular Nanofiber Webs in Nonwoven Scaffolds as Potential Filter Media. Issue 12 (4th December 2012) - Misslitz, Holger; Kreger, Klaus; Schmidt, Hans‐Werner
<x xml:space="preserve">Abstract</x> Microfiber–nanofiber composites are prepared by in situ formation of supramolecular nanofiber webs based on 1, 3, 5‐benzenetricarboxamides in polymer nonwoven scaffolds. The supramolecular nanofibers are strongly fixed to nonwoven microfibers. These composites are sufficiently stable to be suited for air filtration applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>